An Approach For Detection Of Logical Inconsistency - Yadav, Rinki (2012)

(untitled)
Online responses to multi-criteria decision making questionnaires often contain inconsistencies, due to possible inconsistent interpretations of the questions or the erratic mental states of the respondents. If such inconsistent responses remain undetected and no appropriate corrective actions are taken, the questionnaire outcomes will be less reliable. The main research motivation was to minimize such inconsistent responses by detecting the logically inconsistent responses dynamically. The conventional approaches compute a consistency ratio to quantitatively specify the level of inconsistent responses. However, in most online questionnaires, it is too late to highlight the inconsistency level at the end. They should be flagged out as soon as each inconsistent response surfaces.